2000
DOI: 10.1210/endo.141.9.7636
|View full text |Cite
|
Sign up to set email alerts
|

A Link between Insulin Resistance and Hyperinsulinemia: Inhibitors of Phosphatidylinositol 3-Kinase Augment Glucose-Induced Insulin Secretion from Islets of Lean, But Not Obese, Rats1

Abstract: Wortmannin (5-100 nM), a specific phosphatidyinositol 3-kinase inhibitor, augmented 8 mM glucose-induced insulin secretion from control Sprague Dawley rat islets in a dose-dependent manner. This effect persisted after its removal from the perifusion medium; however, this augmenting effect was reduced by the calcium channel inhibitor nitrendipine or by lowering the glucose level to 3 mM. Wortmannin amplified insulin release induced by the combination of 6 -8 mM glucose plus 1 M carbachol; however, it had no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…What reinforces the controversy around this concept of whether short-term autocrine actions of insulin affect its own secretion are the different experimental outcomes reported by investigators. Early studies observed inhibitory actions of exogenous insulin on insulin secretion [88][89][90][91][92][93], whereas others reported no effects [94][95][96][97][98]; in contrast, recent studies demonstrated that insulin enhances its own secretion following glucose stimulation [75,[99][100][101][102][103]. These discrepancies surrounding short term insulin action on insulin secretion might be due to differences in the experimental preparations used in these studies, such as different concentrations and/or incubation times with exogenous insulin and whether stimulatory concentrations of glucose were present or absent in incubation medium.…”
Section: Positive Actions Of Insulin On Insulin Gene Expression and Imentioning
confidence: 85%
“…What reinforces the controversy around this concept of whether short-term autocrine actions of insulin affect its own secretion are the different experimental outcomes reported by investigators. Early studies observed inhibitory actions of exogenous insulin on insulin secretion [88][89][90][91][92][93], whereas others reported no effects [94][95][96][97][98]; in contrast, recent studies demonstrated that insulin enhances its own secretion following glucose stimulation [75,[99][100][101][102][103]. These discrepancies surrounding short term insulin action on insulin secretion might be due to differences in the experimental preparations used in these studies, such as different concentrations and/or incubation times with exogenous insulin and whether stimulatory concentrations of glucose were present or absent in incubation medium.…”
Section: Positive Actions Of Insulin On Insulin Gene Expression and Imentioning
confidence: 85%
“…Nevertheless, the role of growth factor signaling through PI 3-kinase as related to insulin secretion remains poorly understood. Additional difficulties arise because, against expectation, knockout of the gene encoding the p85α subunit of PI 3-kinase results in increased insulin secretion (27), consistent with studies using PI 3-kinase inhibitors (28). Because of the known relationship between IGF and PI 3-kinase signaling and results indicating that IGFs inhibit insulin secretion (29)(30)(31), we sought to examine in mutant mice the contribution of type 1 IGF receptor (IGF1R) function to insulin secretion and β cell proliferation, which could differ from that of the IR pathway.…”
Section: Introductionmentioning
confidence: 84%
“…The concept that insulin affects its own secretion is not new, however, the area is still controversial and currently under discussion. Historically, insulin secretion was suggested to be inhibited by secreted insulin [3–7], but on the other hand, similar models used by others fail to support this concept [12–14]. Most interestingly, recent data suggest that secreted insulin may have a positive effect on insulin exocytosis [9–11,27,28,42].…”
Section: Insulin and Insulin Secretionmentioning
confidence: 99%
“…Moreover, there are data showing an increased glucose‐stimulated insulin release after inhibition of PI3 kinase or in islets of p85 −/− mice [6,15,54,55], indeed suggesting that insulin has a negative effect on β‐cell stimulus–secretion coupling. Interestingly, Eto et al [54] report that inhibition of PI3 kinase did not interfere with the secretion‐triggered pathway including glucose oxidation, ATP content or [Ca 2+ ] i , but suggest the effect to be distal to the increase in [Ca 2+ ] i .…”
Section: Insulin and Insulin Secretionmentioning
confidence: 99%
See 1 more Smart Citation